2012
DOI: 10.1021/nl303197a
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Nonalloyed State of a Statistical Single Atomic Layer Semiconductor Alloy

Abstract: Using atomically and momentum resolved scanning tunneling microscopy and spectroscopy, we demonstrate that a two-dimensional (2D) √3 × √3 semiconducting Ga-Si single atomic alloy layer exhibits an electronic structure with atomic localization and which is different at the Si and Ga atom sites. No indication of an interaction or an electronic intermixing and formation of a new alloy band structure is present, as if no alloying happened. The electronic localization is traced back to the lack of intra alloy bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…One work on a 2D GaÀSi monolayer bound on a Si(111) substrate showed only localized electronic states but no electronic mixing. 18 However, theoretical calculations have shown that 2D alloys, such as hexagonal BNC monolayer 19,20 and transition-metal dichalcogenide monolayer alloys, 21 band gaps. Therefore, experimental work is needed to assess the electronic structure of 2D alloys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One work on a 2D GaÀSi monolayer bound on a Si(111) substrate showed only localized electronic states but no electronic mixing. 18 However, theoretical calculations have shown that 2D alloys, such as hexagonal BNC monolayer 19,20 and transition-metal dichalcogenide monolayer alloys, 21 band gaps. Therefore, experimental work is needed to assess the electronic structure of 2D alloys.…”
mentioning
confidence: 99%
“…Whether alloying can be used to engineer the band gap of 2D materials is still unknown because no atomically thin 2D alloy was obtained. One work on a 2D Ga–Si monolayer bound on a Si(111) substrate showed only localized electronic states but no electronic mixing . However, theoretical calculations have shown that 2D alloys, such as hexagonal BNC monolayer , and transition-metal dichalcogenide monolayer alloys, could have composition-dependent band gaps.…”
mentioning
confidence: 99%
“…Since the surface states extend much farther into the vacuum, their contribution to the tunnel current is significantly larger than that of the bulk states. 35 Thus the band edges observed in the tunneling spectra are determined primarily by the surface states. The observed band onsets and sizes of the gap also support the existence of a Fermi level pinning at both surfaces.…”
mentioning
confidence: 99%